Glutamine Synthetase Sensitivity to Oxidative Modification during Nutrient Starvation in Prochlorococcus marinus PCC 9511 - Gómez-Baena, Guadalupe (PLoS One, 2015)
Glutamine synthetase plays a key role in nitrogen metabolism, thus the fine regulation of this enzyme in Prochlorococcus, which is especially important in the oligotrophic oceans where this marine cyanobacterium thrives. In this work, we studied the metal-catalyzed oxidation of glutamine synthetase in cultures of Prochlorococcus marinus strain PCC 9511 subjected to nutrient limitation. Nitrogen deprivation caused glutamine synthetase to be more sensitive to metal-catalyzed oxidation (a 36% increase compared to control, non starved samples). Nutrient starvation induced also a clear increase (three-fold in the case of nitrogen) in the concentration of carbonyl derivatives in cell extracts, which was also higher (22%) upon addition of the inhibitor of electron transport, DCMU, to cultures. Our results indicate that nutrient limitations, representative of the natural conditions in the Prochlorococcus habitat, affect the response of glutamine synthetase to oxidative inactivating systems. Implications of these results on the regulation of glutamine synthetase by oxidative alteration prior to degradation of the enzyme in Prochlorococcus are discussed.